Chest wall abscess: an atypical presentation of isolated tuberculous liverabscess - Mohanty, D.; Jain, B. K.; Gupta, A.; Agrawal, V. (Acta Biomedica Atenei Parmensis, 2009)
The incidence of hepatic tuberculosis is increasing with the resurgence of tuberculosis due to the emergence of multi drug resistant strains and to an increased prevalence of human immune-deficiency virus infection. In contrast, isolated tuberculous liver abscess (TLA) is extremely uncommon with a prevalence of 0.34% in patients with hepatic tuberculosis. We describe a case of isolated TLA in a 32-year-old immune-competent man, who presented with a painless lump in the right posterior chest wall. Fine needle aspiration revealed acid fast bacilli (AFB), computed tomogram of the thorax showed a hepatic abscess in the segments 6 and 7 communicating with the posterior chest wall. The presentation of TLA may be atypical and diagnosis remains elusive unless hepatic involvement is revealed by imaging and AFB is demonstrated in the aspirated pus or necrotic material. Open drainage of the superficial component of the abscess along with anti- tuberculosis treatment resulted in the resolution of the abscess.